2020
DOI: 10.21742/ijswpm.2020.7.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Gotong Royong in Organization

Abstract: Gotong royong is an original term from Indonesia which means cooperation among society members. Gotong royong is the culture value of the Nusantara (before the establishment of the Indonesian country) since the Neolithic era from 6000 BC, the core of Pancasila (the ideology of the Indonesian country), and plays a role in the government, public and private sectors. There have been many studies of gotong royong in the government and society sectors. But it is still rarely done in the private sector, especially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Observable moral measures are abstract and are contained in a critical mind and conscience (do good) (Arsetyo, 2021;Fauzia, 2017;Is & Jemmi Angga Saputra, 2021;Mahmud et al, 2021). A corporation with this level of morality will be sensitive to environmental issues, so without any obligation or Law, this sensitivity will direct the Corporation into appropriate and wise actions manifested in the participation and implementation of all forms of community social activities, to help and support the potential of the surrounding environment or prevent the decline of social aspects of society (Bahagia et al, 2020;Dimyati et al, 2017;Simarmata et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Observable moral measures are abstract and are contained in a critical mind and conscience (do good) (Arsetyo, 2021;Fauzia, 2017;Is & Jemmi Angga Saputra, 2021;Mahmud et al, 2021). A corporation with this level of morality will be sensitive to environmental issues, so without any obligation or Law, this sensitivity will direct the Corporation into appropriate and wise actions manifested in the participation and implementation of all forms of community social activities, to help and support the potential of the surrounding environment or prevent the decline of social aspects of society (Bahagia et al, 2020;Dimyati et al, 2017;Simarmata et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Menurut Kemendikbud (2017) yang dimaksud nilai gotong royong adalah tindakan menghargai semangat kerjasama dan bahu membahu menyelesaikan persoalan bersama, menjalin komunikasi dan persahabatan, memberi bantuan/pertolongan pada orang-orang yang membutuhkan. Gotong royong didasarkan pada semangat dan kesadaran bahwa dengan bekerja sama, beban yang ditanggung akan menjadi ringan dan tujuan bersama semakin mudah diraih (Simarmata, Yuniarti, Riyono, & Patria, 2020). Gotong Royong dalam novel Roro Mendut merupakan representasi dari kerja sama untuk mencapai sebuah tujuan bersama.…”
Section: Gotong Royongunclassified
“…Wati & Hidayah (2017) reported that cooperation is a form of work carried out together to achieve the desired result. Cooperation activities belong to the original tradition of the Indonesian state which means cooperation between communities (Simarmata et al 2020). Cooperation activities are carried out voluntarily without any coercion (Bintari & Darmawan, 2016).…”
Section: Introductionmentioning
confidence: 99%